PENGARUH PENERAPAN ETIKA BISNIS ISLAM TERHADAP CUSTOMER RETENTION PADA BAITUL MÄ€L WAT TAMWIL (BMT) TUMANG BOYOLALI - Wakhidah, Zahrotul (El-Hayah, 2018)
Abstract : Baitul MÄl wat Tamwil (BMT) as one of the community's choices related to shariah financial institutions increasingly faces greater challenges. Due to the increasingly intense competition faced, Baitul MÄl wat Tamwil (BMT) requires to improve service performance and strengthen the market segment in order to compete with other financial institutions. Good service performance can be supported through the application of Islamic business ethics. This study aims to examine the effect of the application of Islamic business ethics consisting: unity (tawhid), justice ('adl), free will, responsibility, and truth to customer retention in Baitul MÄl wat Tamwil (BMT) Tumang Boyolali, either partially or simultaneously.This research was conducted in Baitul MÄl wat Tamwil (BMT) Tumang branch in Boyolali on June 2017. Data were collected from questionnaires distributed to 100 members by accidental sampling method, then analyzed data obtained by quantitative and qualitative. Quantitative analysis includes descriptive statistical test, validity and reliability test, classic assumption test, hypothesis test through t test, F test and coefficient of determination test (R2) applying program of SPSS 21.0. Qualitative analysis is the interpretation of the data obtained in the study that has been implemented by giving information and explanation.The results showed that all variables of Islamic business ethics have a positive and significant impact on customer retention. Based on multiple linear regression analysis can be concluded that: 1) unity (tawhid) has a positive effect on customer retention of 0.175; 2) justice (â€˜adl) has a positive effect on customer retention of 0.137; 3) free will has positive effect to customer retention of 0,072; 4) responsibility has a positive effect on customer retention of 0.160; 5) truth has a positive effect on customer retention of 0.427; and 6) unity (tawhid), justice (â€˜adl), free will, responsibility and truth simultaneously affect on customer retention by 61.6%. Therefore, improving the application of Islamic business ethics in every operational activity is able to improve customer retention in an institution.Keywords : Islamic business ethics, unity (tawhid), justice ('adl), free will, responsibility, truth, customer retention